PERANCANGAN MODEL PEMBERDAYAAN MASYARAKAT MISKIN DI DAERAH RAWAN BENCANA KECAMATAN SELO KABUPATEN BOYOLALI SEBAGAI UPAYA UNTUK MEWUJUDKAN AGROWISATA PETERNAKAN - Shanti Emawati; Ayu Intan Sari; Endang Tri Rahayu; Aqni Hanifa (Universitas Sebelas Maret, 2011)
The purpose of this study was to determine the level of empowerment of the poor in disaster-prone areas Selo Sub District and produce a model formulation of the empowerment of the poor in an effort to realize the optimization potential of agro farms with local resources. Expected outcomes of this research is the publication of scientific journal of local/national and the formulation of a model of empowerment of the poor in disaster-prone areas as an effort to create the livestock agrotourism. The method to determine the location and sampling of respondents is to cluster sampling technique (sampling area). This research uses research explanations. To determine the empowerment of communities to use the method of Participatory Rural Appraisal (PRA) and Rapid Rural Appraisal (RRA). PRA and RRA is a method that puts the community as researchers, planners, implementers, as the appraisal of development programs so that researchers and stakeholders who are involved as facilitators and community as the implementer. Data collection technique is observation, documentation, interviews and focus group discussion (FGD). Data analysis in the formulation of a model of empowerment of the poor in disaster-prone areas as an effort to create livestock agrotourism by Pearson correlation analysis, multiple linear regression analysis, path analysis method, the process of empowerment of citizens and SWOT analysis. The results of this research is already done survey research sites to see the condition of the villages that will be studied. A visit to the village government for approaching the village officials. In order to dig up information to determine the profile, potential and problems faced by each of the villages have been carried out PRA. However, due to the catastrophic eruption of Merapi volcano constraints, the implementation of the research has not been resolved.